RESEARCH ON THE OPTIMAL DESIGN METHOD OF TYPICAL PROJECTILE STRUCTURES UNDER THERMAL-MECHANICAL COUPLING CONDITIONS - TANG QiQin; LI BoYang; SHI YunGuo; WANG GuoLi (Jixie qiangdu)
Aerodynamic heat often plays a crucial role in the structural performance of some typical projectiles. Based on the structure performance constraints,the present paper aimed at developing a structural optimal design method to reduce the weight of typical projectiles under thermal-mechanical coupling conditions. By virtue of integrating ANSYS into ISIGHT optimization platform,and using APDL parametric modeling technology of ANSYS as well as thermal-mechanical coupling load analysis technology,the simulation model of the structure of typical projectiles was established. Results of the numerical example show that the typical projectile structures may have a 19. 8% reduction in weight with the requirements of strength and rigidity satisfied in a limit value. The rationality of the model and the validity of the method were verified by effective loss in weight. The present work can also provides insight into model establishment and optimal design of typical projectile structures.